Calprotectin in Chronic Inflammatory Demyelinating Polyneuropathy and Variants—A Potential Novel Biomarker of Disease Activity - Stascheit, Frauke; Hotter, Benjamin; Klose, Sarah; Meisel, Christian; Meisel, Andreas; Klehmet, Juliane (Frontiers in Neurology, 2021)
In chronic inflammatory demyelinating polyneuropathy (CIDP) there is an urgent need for biomarkers, to monitor ongoing disease activity. Serum calprotectin (CLP) is inducing signaling pathways involved in inflammatory processes and has been shown to correlate with markers of disease activity in other autoimmune disorders. Thus, we wanted to study the potential value of CLP in comparison to serum neurofilament light chain (sNfl) to monitor disease activity. Sera from 63 typical and atypical CIDP and 6 MMN patients with varying degree of disease activity were analyzed in comparison with 40 healthy controls (HC) in a cross-sectional design. Association of CLP and sNfl levels with socio-demographics, disease duration, CIDP disease activity scale (CDAS), anti-ganglioside antibody (aGAAbs) and impairment status (medical research council-sum score [MRC-SS, the inflammatory neuropathy cause and treatment disability score [INCAT-DS], grip strength, maximum walking distance), patient reported outcome (PRO) parameters (SF-36 questionnaire, Beck’s depression index [BDI], fatigue severity scale [FSS]), as well as treatment regime were investigated using uni- and multivariate analysis. CLP and sNfl levels were significantly higher in all CIDP patients compared to HC (p=0.0009) with an area under the receiver operating curve (AUC) of 0.814 (95% confidence interval (CI) 0.64-0.85) for CLP. Multivariate analysis adjusted for age and gender revealed that CLP acts as an independent predictor for CIDP and MMN. CLP was significantly associated with active disease course according to CDAS and correlated with MRC-SS, whereas sNfl correlated with parameters of disease impairment. There was no correlation with PRO, except for sNfl and the mental health composite score. Subgroup analysis revealed no differences between typical CIDP and atypical variants and aGAAbs-status. CLP was elevated in CIDP and variants and was associated with active disease course, whereas sNfl shows further potential as biomarker of axonal degeneration. Thus, CLP might be a suitable additive biomarker for measurement of ongoing inflammation, which is greatly needed to guide better patient care in CIDP